2008
DOI: 10.1097/01.won.0000308622.86508.8d
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Hospital-Acquired Heel Ulcer Rates in an Acute Care Facility

Abstract: The intervention did not appear to receive adequate staff nurse support needed to make the project successful. Factors that influenced the lack of support may have included: (1) educational method used, (2) lack of organization approved, evidenced-based standardized protocols for prevention and treatment of heel ulcers, and (3) failure of facility management to convey the importance as well as their support for the project.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Pressure ulcers are a mostly avoidable incidence. [ 12 ] Research has shown that when nursing staff are educated and knowledgeable on pressure ulcer prevention, nursing practice can then change and improve[ 13 ] According to Land,[ 14 ] pressure ulcer prevention is such a vital recurring aspect of nursing care that many staff fail to concede its importance and consequence in maintaining standards of care. Conversely, evidence has shown that patient acuity and nursing assignments have amplified in the last 30 years.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pressure ulcers are a mostly avoidable incidence. [ 12 ] Research has shown that when nursing staff are educated and knowledgeable on pressure ulcer prevention, nursing practice can then change and improve[ 13 ] According to Land,[ 14 ] pressure ulcer prevention is such a vital recurring aspect of nursing care that many staff fail to concede its importance and consequence in maintaining standards of care. Conversely, evidence has shown that patient acuity and nursing assignments have amplified in the last 30 years.…”
Section: Introductionmentioning
confidence: 99%
“…[ 17 ] Pressure ulcers are complex wounds requiring an overabundance of skills and knowledge to manage and care for. [ 12 ] There are many policies and guidelines on pressure ulcer prevention and management. [ 7 , 19 ] Regrettably, studies have shown that many qualified staff nurses do not adhere to these guidelines or evidence based practice, leading to insufficient pressure ulcer prevention practice.…”
Section: Introductionmentioning
confidence: 99%